Analysis of Mobile JKN Service Quality on BPJS User Satisfaction at Arjasa Public Health Center Jember - Sahrudi Hidayat; Indria Yuli Susanti; Yusita Titi Hapsari (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study investigates the empirical impact of Mobile JKN service quality on BPJS participant satisfaction at the Arjasa Public Health Center, Jember Regency, a inquiry prompted by persistent impediments in digital health delivery notably systemic errors, constrained responsiveness, and disparities in public digital literacy. Employing a quantitative approach with an explanatory research design, data were gathered through structured questionnaires from 100 purposively sampled respondents. Methodologically, the dataset was evaluated via multiple linear regression using SPSS version 25, operationalizing the five core SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The empirical findings reveal that Mobile JKN service quality exerts a positive and statistically significant influence on user satisfaction, both partially and simultaneously. Notably, the reliability dimension emerged as the most dominant determinant of satisfaction, highlighting the critical role of application stability. These insights underscore the imperative for healthcare administrators to optimize system architecture, digital infrastructure stability, data privacy protocols, and institutional responsiveness. Consequently, future scholarly inquiries are encouraged to integrate external frameworks, such as digital literacy levels and technology acceptance models, to provide a more holistic evaluation of the m-Health ecosystem.